Size divergence and dietary partitioning enhance coexistence of two herbivorous species of Diaptomus (Copepoda: Calanoida) in some shallow Quebec lakes - Chow-Fraser P; Maly EJ (Canadian Science Publishing, 1992)
Diaptomus minutus and Diaptomus oregonensis overlapped extensively in their vertical and temporal distributions and were positively associated within and among lakes. Although size displacement could not be detected when body lengths of sympatric and allopatric populations were compared, in lakes where there was a reduction in size overlap between species, the two species coexisted at relatively high densities. This contrasted with situations where convergence in size between species was accompanied by a limited abundance of one or both diaptomids. D. minutus, the smaller copepod, preferentially ingested a number of small algal particles (<10 μm), whereas D. oregonensis tended to ingest a greater number of larger particles. Although preference for small algae (Selenastrum and small blue-green algae) was negatively correated with prosome length, preference for larger alga taxa (Planktosphaerium, centric diatoms such as Melosira, and Achnanthes) was positively correlated with diaptomid size. There were, however, differences with respect to the degree of diet overlap between species in the two lakes, reflected in a significant negative correlation between dietary and size overlap. Observations are consistent with the hypothesis that reduction in size overlap has resulted in reduced exploitative competition, and that divergence in size and diet may be the mechanism that allows D. minutus and D. oregonensis to coexist when food becomes limiting. -from Authors
Keywords: 31 Biological Sciences; 3103 Ecology; Nutrition